Third-Generation Sequencing Reveals LncRNA-Regulated HSP Genes in the Populus x canadensis Moench Heat Stress Response - Xu, Jiahong; Fang, Meng; Li, Zhihao; Zhang, Maoning; Liu, Xiaoyu; Peng, Yuanyuan; Wan, Yinglang; Chen, Jinhui (Frontiers in Genetics, 2020)
Long non-coding RNAs (lncRNAs) regulate plant responses to abiotic stresses. However, the short reads produced by second-generation sequencing technology make it difficult to accurately explore full-length transcripts, limiting the study of lncRNAs. In this study, we used third-generation long-read sequencing technology with the PacBio Sequel and Illumina platform to explore the role of lncRNAs in the heat stress response of Populus x canadensis Moench trees. We using 382,034,416 short reads to correct 4,297,179 long reads by resulted in 23 66,657 full-length transcripts, representing 33,840 genes. Then, 753 putative lncRNAs were identified, including 658 sense lncRNAs (87.38%), 41 long intervening/intergenic noncoding RNAs (lincRNAs) (5.44%), 12 antisense lncRNAs (1.59%), and 42 sense intronic lncRNAs (5.58%). Using the criteria |log2FC| ≥ 1 and q-value < 0.05, 3,493 genes and 78 lncRNAs were differentially expressed under the heat treatment. Furthermore, 923 genes were detected as targets of 43 differently expressed lncRNAs by cis regulation. Functional annotation demonstrated that these target genes were related to unfolded protein binding, response to stress, protein folding, and response to stimulus. Lastly, we identified a lncRNA–gene interaction network consisting of 4 lncRNAs and 6 genes (Heat Shock Protein 82 (HSP82), HSP83, Disease Resistance Protein 27 (DRL27), DnaJ family protein (DNJH), and two other predicted protein-coding genes), which showed that lncRNAs could regulate HSP family genes in response to heat stress in Populus. Therefore, our third-generation sequencing has improved the description of the P. canadensis transcriptome. The potential lncRNAs and HSP family genes identified here present a genetic resource to improve our understanding of the heat-adaptation mechanisms of trees.